Is it safe to use a kinetic therapy bed for care of patients with cervical spine injuries?. Issue 2 (February 2015) - Prasarn, Mark L.; Horodyski, MaryBeth; Behrend, Caleb; Del Rossi, Gianlucca; Dubose, Dewayne; Rechtine, Glenn R.
Abstract Introduction Bedrest is often used for temporary management, as well as definitive treatment, for many spinal injuries. Under such circumstances patients cannot remain flat for extended periods due to possible skin breakdown, blood clots, or pulmonary complications. Kinetic therapy beds are often used in the critical care setting, although this is felt to be unsafe for turning patients with spine fractures. We sought to evaluate whether a kinetic therapy bed would cause as much spinal motion at an unstable cervical injury as occurs during manual log-rolling on a standard intensive care unit bed. Methods Unstable C5–C6 ligamentous injuries were surgically created in 15 fresh, whole cadavers. Sensors were affixed to C5 and C6 posteriorly and electromagnetic motion tracking analysis performed. In all cases a cervical collar was applied by an orthotist after creation of the injury. The amount of angular motion and linear displacement that occurred at this injured level was measured during manual log-rolling and patient turning using a kinetic therapy bed. For statistical analysis, the range of motion for angles about each axis and displacement in each direction was analyzed by multivariate analysis of variance with repeated measures. Results When comparing manual log-rolling and kinetic bed therapy, significantly more angular motion was created by the log-roll manoeuvre in flexion–extension (p = 0.03) and lateral bending (p = 0.01). There was no significant difference in axial rotation between the two methods (p = 0.80). There were no significant differences demonstrated in medial–lateral and anterior–posterior translation. There was almost two times the axial displacement between manual log-rolling and the kinetic therapy bed and this reached statistical significance (p = 0.05). Conclusion There is less motion at an unstable cervical injury in flexion–extension, lateral bending, and axial displacement when turning a patient using a kinetic therapy bed as opposed to traditional manual log-rolling. It may be preferable to use a kinetic therapy bed rather than manual log-rolling for patients with cervical spine injuries to decrease unwanted spinal motion. In addition, it may be easier and less physically demanding on nursing staff that must regularly turn the patient if manual log-rolling is implemented.